The Effect of Warm Water Compresson Breast Milk Production Postpartum Mothers at Juliana's Independent Midwifery Practice - Pardede, Desika Wali; Meriati Bungal Arta Purba; Yunita Sari Purba (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Background: The smooth process of breast milk (ASI) production and secretion is often an obstacle for postpartum mothers, and this condition can affect the success of the exclusive breastfeeding program. One of the non-pharmacological approaches that can be applied to overcome this problem is by giving warm compresses to the breast areola area. Objective: This study aims to evaluate the effect of warm compresses on breast milk secretion in postpartum mothers at the independent midwifery practice of Juliana. Method: This study used a pre-experimental design with a one-group pretest-posttest model. A total of 35 postpartum mothers were selected as samples using purposive sampling techniques. The Shapiro-Wilk normality test showed that the data were not normally distributed; therefore, hypothesis testing was conducted using the Wilcoxon Signed-Rank test. Results: Before the intervention, all respondents (100%) experienced insufficient breast milk secretion. After applying warm compresses, 28 respondents (80%) showed improvement with smooth milk secretion. The Wilcoxon test yielded a value of Z = -5.292 and p-value = 0.000 (p < 0.05), indicating a significant difference before and after the intervention. Conclusion: The administration of warm compresses proved to have a significant effect on improving breast milk secretion in postpartum mothers. This intervention can serve as a simple, effective, and easily applicable non-pharmacological alternative to support successful breastfeeding.